Zebrafish Patient‐Derived Avatars from Digestive Cancers for Anti‐cancer Therapy Screening. Issue 4 (18th April 2022) - Costa, Bruna; Estrada, Marta F.; Barroso, Mariana Tavares; Fior, Rita
Abstract: Patient‐derived xenografts (PDXs), also called "avatars, " are generated by the implantation of human primary tumor cells or tissues into a host animal. Given the complexity and unique characteristics of each tumor, PDXs are models of choice in cancer research and precision medicine. In this context, the zebrafish PDX model (zPDX or zAvatar) has been recognized as a promising in vivo model to directly challenge patient cells with anti‐cancer therapies in a personalized manner. The assay relies on the injection of tumor cells from patients into zebrafish embryos to then test and identify the best available drug combination for a particular patient. Compared to mouse PDXs, zAvatar assays take less time and do not require in vitro or in vivo cell expansion. The present article describes how to generate zAvatars from resected digestive cancer from surgeries and how to then use them for anti‐cancer therapy screening. We describe the steps for tumor sample collection and cryopreservation, sample preparation and fluorescent labeling for microinjection into zebrafish embryos, drug administration, and analysis of tumor behavior by single‐cell confocal imaging. We provide detailed protocols and helpful tips for performing this assay, and we address the technical challenges associated with the workflow. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Patient tumor sample collection and cryopreservation Basic Protocol 2 : Generation of zAvatars and anti‐cancer treatment Basic Protocol 3 : Whole‐mount immunofluorescence Basic Protocol 4 : Confocal imaging and analysis